2019
DOI: 10.1089/cmb.2018.0162
|View full text |Cite
|
Sign up to set email alerts
|

BPscore: An Effective Metric for Meaningful Comparisons of Structural Chromosome Segmentations

Abstract: Studying the 3D structure of chromosomes is an emerging field flourishing in recent years because of rapid development of experimental approaches for studying chromosomal contacts. This has led to numerous studies providing results of segmentation of chromosome sequences of different species into so called Topologically Associating Domains (TADs). As the number of such studies grows steadily and many of them make claims about the perceived differences between TAD structures observed in different conditions, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…These observations are suggestive of different modes of dynamic changes in co-expression domains, with low SLE activity genomes characterized by DCE fragmentation and high activity ones featuring a redistribution of co-expression with increased percentages of expanded and emerged DCEs. This redistribution was also supported by a simple value measure of DCE pattern similarity, calculated with the implementation of BPscore (26), which showed that in spite of being comparable in genome coverage, the DCEs between high activity patients and healthy controls were radically different in terms of genomic localization (Supplementary Figure 2).…”
Section: Dces Are Dynamically Redistributed In Slementioning
confidence: 62%
“…These observations are suggestive of different modes of dynamic changes in co-expression domains, with low SLE activity genomes characterized by DCE fragmentation and high activity ones featuring a redistribution of co-expression with increased percentages of expanded and emerged DCEs. This redistribution was also supported by a simple value measure of DCE pattern similarity, calculated with the implementation of BPscore (26), which showed that in spite of being comparable in genome coverage, the DCEs between high activity patients and healthy controls were radically different in terms of genomic localization (Supplementary Figure 2).…”
Section: Dces Are Dynamically Redistributed In Slementioning
confidence: 62%
“…2b ). We also employed two different indexes, BP score (BP) [ 52 ] and variation of information (VI) [ 38 ]. Although IS performed best with the two indexes (Additional file 2 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given two sets of domains, T = { T 1 , T 2 , …, T n } and K = { K 1 , K 2 , …, K m }, N is the length of contact matrix. We assess their similarity using adjusted mutual information (AMI) [ 51 ], weighted similarity (WS) [ 42 ], BP distance (BP) [ 52 ], and variation of information (VI) [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…To determine the maximum window size for TAD calls, TAD calls were compared across window sizes for the same patient using the BPscore metric 78 . TAD calls are identical when the BPscore is 0, and divergent when 1.…”
Section: Tad Identificationmentioning
confidence: 99%